Investigation of blood lactate levels, hearth rates and technical performance of hearing-impaired elite male Greco-Roman wrestlers - Kivrak, A. O.; Pepe, S. (Journal of Education and Training Studies, 2019)
This study was conducted with hearing-impaired elite greco-roman wrestlers to determine the relationships and variations in heart rates (HR), blood lactate (La) levels and number of performances during the maximal effort and recovery periods. Voluntary 8 hearing-impaired elite male wrestlers with an average age of 21,75±2,05 years participated into present experiments. Resting heart rates of the athletes were determined before the maximal effort, blood samples were taken for lactate levels, athletes took warm up and stretching exercises for 15 minutes. For maximal effort, athletes performed hip-headlock throw technique for 2 minutes in 3 periods. Proper performances were counted and heart rates were measured in between the periods. To determine recovery characteristics of the athletes after maximal effort, HR and La levels were determined at 3rd, 15th and 30th minutes after maximal effort.